From income poverty to multidimensional poverty: An international comparison - Francesco Burchi; Nicole Rippin; Claudio Montenegro (International Policy Centre for Inclusive Growth (IPC-IG), 2018)
The United Nations 2030 Agenda for Sustainable Development clearly recognises that poverty is more than just the lack of a sufficient amount of income. However, some scholars argue that an income-based measure of poverty can sufficiently capture poverty in other dimensions. Unfortunately, the available international indicators of multidimensional poverty suffer from several weaknesses and cannot be directly compared with monetary measures of poverty. This paper provides two main contributions to the literature on poverty measurement and analysis. First, it proposes a theoretically and methodologically sound indicator of multidimensional poverty, called the Global Correlation Sensitive Poverty Index (G-CSPI), which addresses most of the problems present in other poverty indicators. Thanks to the massive I2D2 database of harmonised household surveys, the G-CSPI was calculated for more than 500 surveys, and the results show that it is stable and robust. Second, for the first time we were able to conduct a comparative analysis between income and multidimensional poverty, relying on the same dataset to calculate both. Previous cross-country evidence was based on very different surveys used for the computation of income and multidimensional poverty and even conducted in different years. Building on recent data for 92 countries, our analysis shows that the headcount ratio of extreme monetary poverty (USD1.90) is highly correlated with that of the G-CSPI, but that the relationship is clearly non-linear. Thus we provided the first empirical evidence of the fact that income poverty is not a sufficiently good proxy for multidimensional poverty.
Keywords: 330; Income; poverty; multidimensional; international; comparison